Higher Education Institution Students’ Attitude Towards Communicative Language Teaching, Anxiety, and Learning Strategy - Cabansag, John N. (Migration Letters, 2023)
The research paper endeavored to determine the attitude of the students toward Communicative Language Teaching (CLT), level of language anxiety, language learning strategies utilized by the learners and the relationship between language learning strategies and (a) attitude towards communicative language teaching and (b) language anxiety. The respondents of the study were the students of higher education institutions in Northern Philippines, School Year 2022-2023. Three instruments were used, (a) the Communicative Language Teaching Attitude Scale (COLTAS), (b) Foreign Language Classroom Anxiety Scale (FLCAS), and (c) a modified Strategy Inventory of Language Learning (SILL). Statistical Package for the Social Sciences (SPSS) was used in processing the data and Kendall’s tau-b correlation coefficient was used to determine the correlation between the variables. The results indicate that the respondents have favorable attitude towards CLT with some reservations and high-intensity language anxiety. Furthermore, the results revealed that the respondents usually use 13 out of the 18 language learning strategies presented in SILL, with the exemption of 5 which are only used occasionally. However, out of the 18 strategies mentioned, only 11 implied a significant and indirect association between the attitude towards CLT and language learning strategies. Furthermore, the study revealed a significant and direct association between the use of language learning strategies and language anxiety levels. Hence, the hypothesis “there is no significant relationship between language learning strategies and (a) attitude towards communicative language teaching, and (b) language anxiety of the respondents” is rejected. The study has proven that Communicative Language Teaching (CLT) can address the passive attitude of learners in an English class, and it is a feasible teaching approach that can certainly be applied in the ESL context. Students’ concerns about active speech roles and teachers’ desire for them to move away from passive learning appear to fit well into the 21st-century learner-centered philosophy. The results of the study pave way to adhering to the principles of eclectic method of second language teaching-learning wherein teachers need to consider the social milieu, interests, experiences, motivation, and anxiety level of learners. This paper provides a wider perspective on the interplay of the principles of Communicative Language Teaching (CLT), foreign language anxiety and learning strategy in an EFL/ESL classroom in the 21st century.